Innovative approaches to CAR-T cell therapy: the role of lipid metabolism pathways - Minjie Guo; Yuting Zhang; Xiao Yuan; Xu Wang (Journal of Translational Medicine)
Abstract The efficient response structure of chimeric antigen receptor T (CAR-T) cells has led to significant success in the treatment of hematological malignancies. However, when confronted with the challenges associated with solid tumors, CAR-T cells have increasingly exhibited limitations, including inadequate infiltration and a shortened lifespan. Consequently, enhancing CAR-T cells to broaden their applicability across a wider range of malignancies has emerged as an urgent priority. Nutrient metabolism is integral to the entire lifecycle of CAR-T cells, with lipid metabolism serving as a critical pathway for sustaining the energy supply of memory T cells. This aspect is essential for the long-term survival of CAR-T cells and underpins their overall efficacy. This article aims to explore the impact of tumors on T-cell lipid metabolism, drawing on existing research findings, and analyzing strategies for improving CAR-T cells from this perspective. It is hoped that this investigation will provide new insights for enhancing the efficacy of CAR-T cell therapies.